DEPARTMENT OF INTERNATIONAL RELATIONS OF THE RELIGIOUS CONTROL OF THE SOVIET UNION (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
In this article, the 4 Muslim religious control leaders established in the USSR established the Department of International Relations to exchange their views on international politics, to further improve and improve relations with foreign guests, tourists and foreign press reporters, about its goals and objectives. information is provided.